2010
DOI: 10.1039/b920455e
|View full text |Cite
|
Sign up to set email alerts
|

Western Mediterranean coastal waters—Monitoring PCBs and pesticides accumulation in Mytilus galloprovincialis by active mussel watching: the Mytilos project

Abstract: In order to evaluate the contamination levels in the Western Mediterranean basin, the active mussel watch methodology has been applied. This methodology consists of mussel transplantation (Mytilus galloprovincialis) from non impacted areas to selected coastal areas, characterised by potential impact from the continent due to contaminating sources. The areas of interest were selected along the entire coastal development of the Western Mediterranean sea, 122 sites in total. The time of mussel caging exposure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 40 publications
(65 reference statements)
5
27
0
Order By: Relevance
“…This hypothesis is confirmed by data previously published by Song et al [37]. PCBs and pesticides detected in Asinara are high compared to the literature, since Scarpato et al [38] showed medium levels of contamination in this area in the North of Sardinia. The plankton taxa did not suggest any direct connection with MP, and showed a different composition at both levels, the surface layer (MA) and the deeper one (WP2) ( Figure 5).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This hypothesis is confirmed by data previously published by Song et al [37]. PCBs and pesticides detected in Asinara are high compared to the literature, since Scarpato et al [38] showed medium levels of contamination in this area in the North of Sardinia. The plankton taxa did not suggest any direct connection with MP, and showed a different composition at both levels, the surface layer (MA) and the deeper one (WP2) ( Figure 5).…”
Section: Discussionsupporting
confidence: 81%
“…This is in accordance with previous studies where PCB 110 and PCB 138 showed the highest percentages in China, and PCB 138, PCB 153, PCB 180 were the most common in Greece and Portugal [35]. However, our results slightly differ from what is generally detected in environmental samples, particularly for biota and sediment, where the PCB 153 and 138 are usually the predominant ones [38]. The sum of DDs (dichloro diphenyls) for the sea surface showed values ranging from 271 ng/g for Asinara to 9.89 ng/g for Tremiti, whereas, for the deep layer, the values ranged from 91.5 ng/g for Asinara to 5.78 ng/g for Ischia.…”
Section: Discussionsupporting
confidence: 46%
“…Khaled et al (2004) reported levels of 6.75 to 66.4 ng•g -1 ww in mussels collected along the Egyptian Red Sea coast. Scarpato et al (2010) detected total PCBs in mussels from the coasts of the western Mediterranean Sea ranging from 5 to 60 ng•g -1…”
Section: Discussionmentioning
confidence: 99%
“…These methods are based mainly on United States Environmental Protection Agency (USEPA) methods (e.g., 8270C, 1614, 1668) [19,24,[34][35][36].…”
Section: Organic Pollutantsmentioning
confidence: 99%